2-Generator arithmetic Kleinian groups III - Conder, M. D. E.; Maclachlan, C.; Martin, G. J.; O’Brien, E. A. (MATHEMATICA SCANDINAVICA, 2002)
This paper forms part of the program to identify all the 2-generator arithmetic Kleinian groups. Here we identify all conjugacy classes of such groups with one generator parabolic and the other generator elliptic. There are exactly 14 of these and exactly 5 Bianchi groups in their commensurability class, namely PSL(2,O_d) for d=1,2,3,7 and 15. This complements our earlier identification of the 4 arithmetic Kleinian groups generated by two parabolic elements.